ChemInform Abstract: Baeyer—Villiger Reaction in Different Catalysis. Issue 3 (21st January 2014) - Yan, Fanyong; Li, Chuying; Liang, Xiaole; Guo, Shanshan; Fu, Yang; Chen, Li
Abstract Review: 102 refs.